HIGH RESOLUTION U-PB DATING OF MIDDLE TRIASSIC VOLCANICLASTICS: TIME-SCALE CALIBRATION AND VERIFICATION FOR TUNING PARAMETERS FOR CARBONATE SEDIMENTATION - Mundil R.; Brack P.; Meier M.; Rieber H.; Oberli F. (My University, 1996)
We report high-resolution single-zircon UPb age data for Middle Triassic volcaniclastic intercalations in biostratigraphically calibrated pelagic successions of the Southern Alps. The results require a redefinition of the chronometric scale for the Middle Triassic. Moreover, they do not support current models relating cyclic sedimentation in platform carbonates of the Dolomites to orbital tuning.Tight concordant age clusters were obtained for five volcaniclastic layers in three ammonoid biozones of late Anisian to early Ladinian age. Two layers in the (Nevadites) Secedensis Zone yielded identical mean ages of 241.2 + 0.8/−0.8 Ma and 241.2 + 0.8/−0.6 Ma (errors given at the 95% confidence level). A layer in the Gredleri Zone is dated at 238.8 + 0.5/−0.2 Ma, and two horizons in the Archelaus Zone yield similar ages of 237.9 + 1.0/−0.7 Ma and 238.0 + 0.4/−0.7 Ma. These results are significantly older than the age values of 233–235 Ma assigned to the Anisian/Ladinian boundary by several current time scales [1–4]. Moreover, our estimate of 240.7–241.3 Ma (depending on biostratigraphic collocation) for the Anisian/Ladinian boundary casts doubts on the reliability of age values of 245–250 Ma proposed by most time scales for the Permian/Triassic boundary.The occurrence of pelagic fossils in basinal sediments as well as in age-equivalent shallow marine Middle Triassic platform carbonates in the Dolomites allows the sedimentary sequences of both environments to be correlated. The 800 m thick Latemar platform (western Dolomites) is characterized by cyclic stacking patterns, which have been interpreted as results of Milankovitch-type high-frequency/low-amplitude sea-level fluctuations. The 12 m.y. interval of platform growth postulated from the assignment of orbital periodicities to the platform carbonate cycles [5,6] is in conflict with a maximum time span of 4.7 m.y. allowed by the present zircon data.
Keywords: Triassic; Мезозой::Триасовая; Mesozoic::Triassic